DRUGI ROZBIÓR I POWSTANIE KOŚCIUSZKOWSKIE W ŚWIETLE KORESPONDENCJI OTTONA HEINRICHA IGELSTRÖMA - VADZIM ANIPIARKOU (Kwartalnik Historyczny)
Otto Heinrich Igelström’s correspondence with Empress Catherine II and her favourite, Platon Zubov, not only provides insight into the details of Igelström’s actions as Russian general en chef and ambassador to the Polish-Lithuanian Commonwealth in 1793–1794, but also allows for a better understanding of Russia’s strategy. The most crucial element of this was the transfer of the majority of the Commonwealth soldiers to Russian service and the use, if necessary, of the Polish-Lithuanian state’s territory after the second partition as the theatre of a possible war between the Russian Empire and Prussia. These plans also show St Petersburg’s disregard for the political costs of its aims, including the risk of an uprising in Poland.